2020
DOI: 10.3889/oamjms.2020.5298
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculosis in Coronavirus Disease-19 Patients: A Report of Two Cases from Nigeria

Abstract: BACKGROUND: Despite the concern on the impact of coronavirus disease (COVID)-19 on tuberculosis (TB), there is a paucity of information from the developing countries inclusive of Nigeria. CASE REPORT: Hence, we report two cases of Nigerian’ adults with coinfections of severe acute respiratory syndrome coronavirus 2 and Mycobacterium tuberculosis (MTB). The two cases were males and aged 30 and 33 years, respectively. They presented with cough, fever, and weight loss with features of acute respiratory symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We identified information concerning treatment after discharge for 10 patients; 8 of them received ATT and 2 received treatment for existing comorbidity. Although there was no doubt that the regimens for TB and COVID-19 coinfected patients were highly heterogeneous, we still could identify four main paradigms about treatment during hospitalisation: (1) simultaneous antiviral treatment and ATT,19–21 23–26 28 30 31 34 35 39–41 43–45 49 51 (2) only ATT,22 26 32 33 35 36 46–48 (3) only antiviral treatment,18 24 26 27 38 44 50 (4) no antiviral treatment and ATT 37. Check online supplemental tables 4 and 5 for detailed information about the treatment.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We identified information concerning treatment after discharge for 10 patients; 8 of them received ATT and 2 received treatment for existing comorbidity. Although there was no doubt that the regimens for TB and COVID-19 coinfected patients were highly heterogeneous, we still could identify four main paradigms about treatment during hospitalisation: (1) simultaneous antiviral treatment and ATT,19–21 23–26 28 30 31 34 35 39–41 43–45 49 51 (2) only ATT,22 26 32 33 35 36 46–48 (3) only antiviral treatment,18 24 26 27 38 44 50 (4) no antiviral treatment and ATT 37. Check online supplemental tables 4 and 5 for detailed information about the treatment.…”
Section: Resultsmentioning
confidence: 96%
“…Until 19 March 2021, there were 35 case reports from 17 countries, including India,18–22 Indonesia,23 China,24–28 Saudi Arabia,29 30 Qatar,31 32 Singapore,33 Turkey,34 35 Haiti,36 Argentina,37 USA,38–41 Brazil,42 43 Panama,44 Nigeria,45 46 South Africa,47 48 Morocco,49 Italy50 51 and France 52. Totally, 55 cases were described in these 35 reports.…”
Section: Resultsmentioning
confidence: 99%
“…However, the case reports and case series (18 studies, 46 cases) identified in the review did highlight certain themes of interest. First, these studies demonstrated that persons admitted for COVID-19 may be diagnosed with active TB during the hospitalization precipitated by COVID-19 [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Final clinical outcomes at the conclusion of TB treatment were generally not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Second, corticosteroid therapy was used in some persons with COVID-19 and TB co-infection. Some reports cited a TB-specific indication for corticosteroids, namely central nervous system TB [ 42 , 43 ], while others reported the use of corticosteroids as primary therapy for COVID-19 [ 33 , 38 , 45 ]. Third, persons with COVID-19 and TB co-infection presented with various comorbidities (HIV, diabetes mellitus, chronic kidney disease) [ 34 , 37 , 44 , 46 ] and complications: hepatotoxicity [ 33 , 35 ]; extension of the duration of standard TB treatment to 9 months [ 32 ]; drug-resistant TB [ 34 , 47 , 48 ]; extrapulmonary TB [ 42 , 43 , 48 ]; and death [ 33 , 38 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary TB patients presented with fever, productive cough, night sweating, weight loss, hemoptysis, dyspnea, fatigue, and loss of appetite (Shanmuganathan and Shanmuganathan, 2015). Some people with COVID-19 were referred to the hospital with characteristic TB symptoms, such as fever, night sweats, weight loss, reduced appetite, and cough with occasional blood-streaked sputum, and further evaluations and tests confirmed the simultaneous presence of MTB and SARS-CoV-2 organisms (Cutler et al, 2020;Gbenga et al, 2020;Singh et al, 2020;Tham et al, 2020;Yadav and Rawal, 2020;Baskara et al, 2021;Musso et al, 2021;Pillay and Magula, 2021). As lung damage caused by TB increases the body's susceptibility to getting infected with other airborne infections, it can be considered that TB can be a risk factor for exacerbating the severity of COVID-19 patients (Mousquer et al, 2020).…”
Section: Clinical Features Of Tuberculosis/ Covid-19 Coinfectionsmentioning
confidence: 99%